Small Town Boy: Neil Bartlett Learns How to Be Gay: Момче од мал град: Нил Бартлет учи како да биде геј - Halperin, David M.; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): David M. Halperin | Дејвид М. Халперин Title (English): Small Town Boy: Neil Bartlett Learns How to Be Gay Title (Macedonian): Момче од мал град: Нил Бартлет учи како да биде геј Translated by (English to Macedonian): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 117-155 Page Count: 38 Citation (English): David M. Halperin, “Small Town Boy: Neil Bartlett Learns How to Be Gay,” Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008): 117-155. Citation (Macedonian): Дејвид М. Халперин, „Момче од мал град: Нил Бартлет учи како да биде геј“, превод од англиски Родна Русковска, Идентитети: списание за политика, род и култура, т. 6, бр. 2-3 (лето 2007 - зима 2008): 117-155.